(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: In some trials in United States of America (USA) and Bangladesh, vasodilating non selective β blockers (e.g. carvedilol, propranolol etc.) have been shown to be better tolerated than nonvasodilating β1 selective blocker (e.g. atenolol, metoprolol etc.) to prevent cardiovascular diseases (Coronary Heart Disease, Ischemic Heart Disease and other cardiovascular conditions) Objective: To compare the role of atenolol and carvedilol in the prevention of adrenaline induced myocardial infarction (MI) in experimental animal (rats). Materials and Methods: This experimental study was carried out in the Department of Pharmacology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka for a period of one year (from July 2014 to June 2015). Seventy two (72) healthy rats of Long Evan Norwegian strains, 3-4 months of ages of both sexes, weight between 180-220g were used. These rats were randomly selected and ethical issues were addressed. In this study cardio-protective effect was assessed by measuring the serum enzymes (CK-MB and AST) levels and antiperoxidative action was estimated by the hepatic and cardiac reduced glutathione (GSH) contents in experimentally (adrenaline) induced myocardial infarction. Results: Adrenaline (2mg/kg) induced myocardial damage in rat model was evaluated biochemically by significant (P<0.001) increase in CK-MB and AST levels. Free radical production following adrenaline induced myocardial infarction was indirectly reflected by significant (P<0.001) depletion in hepatic & cardiac GSH contents. Cardio protection provided by atenolol and carvedilol pretreatment in adrenaline induced myocardial infraction was assessed by significant prevention of increase in serum CK-MB and AST levels. Antioxidant properties of carvedilol & atenolol were evaluated by significantly (P<0.001) increase in and significantly no (NS) change in GSH (hepatic & cardiac) contents respectively. Conclusion: The study indicated that carvedilol (nonselective β blocker) through their antioxidant property in addition to α and β- blocking effect afforded more cardio protection than atenolol (selective β1adrenoceptor blocker) in experimental MI. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 65-70